Effects of different types of feedback of a mobile-assisted learning application and motivation towards mathematics learning on students' mathematics performance. Issue 3 (21st August 2017) - Bringula, Rex; De Leon, Jan Sepli; Rayala, Kharl John; Pascual, Bernadette Anne; Sendino, Kevin
Abstract : Purpose: The purpose of this study is to determine the effects of four different forms of feedback (such as, complete solution, line-by-line correction, line-by-line hint and correct-incorrect final answer) of a mobile-assisted learning application on linear equations and motivation of students towards mathematics learning on students' mathematics performance. Design/methodology/approach: Totally, 285 Grade 7 students (72 students each for the first-three feedback and 69 students for the last feedback) participated in the five-day experiment. A validated instrument was utilized to determine the motivation of students in learning mathematics. Findings: It was revealed that students solved more problems and spent more time in the line-by-line hint type of feedback. The correct-incorrect final answer group had the most number of incorrect problems solved. It was found that the scores of the students would be different from one another after they utilized the app. Nonetheless, all of them learnt significantly from the app. Five steps of hierarchical regression revealed that all types of feedback were consistent predictors of posttest scores. Thus, the first null hypothesis stating that there is no significant difference between the pretest and posttest scores of the students when categorized by different forms of feedback was rejected. The second null hypothesis stating that the four types of feedback and motivation of students do not influence mathematics performance is partially rejected. Research limitations/implications: The study can be replicated in a school with a different atmosphere. Practical implications: The use of the application is highly recommended for students who are beginning to learn linear equations. Teachers can replicate the four types of feedback in an actual classroom setting. Originality/value: It was confirmed that the four types of feedback can teach the students learn mathematics, regardless of the motivation of the students.